IMPLEMENTASI MANAJEMEN SECURITY BERBASIS PANCASILA SEBAGAI LANGKAH PENCEGAHAN TERJADINYA PERSELISIHAN ANTARA NARAPIDANA DI LEMBAGA PERMASYARAKATAN - Daniel Saputra; Edy Soesanto; M Aliffathur Rizki (CV. Adiba Aisha Amira, 2024)
Pancasila is the basis of the Indonesian state with values originating from Indonesian culture and culture, viewing life as an Indonesian way of life and reflecting respect for human dignity and human rights. As an open ideology, Pancasila has the freedom to follow current developments and introduce itto the behavior of Indonesian society. In the case of correctional institutions, the ideal goal is disciplinary and reform initiatives that are primarily based on the values of Pancasila. Prisoner development is a system that includes various elements such as philosophy, legal basis, goals and system approach. Communication is key to fulfilling the prison officer's mission, especially when it comes to effective safety management. The revitalization of correctional administration is aimed at improving the implementation of correctional tasks, objectivity in assessing changes in inmates' behavior, the role of community leaders, security of correctional institutions, and protection of ownership of evidence. However, challenges remain, including a lack of police training, unsafe working conditions, and inadequate facilities. Therefore, this research aims to identify the causes of conflict between prisoners, assess the implementation of security controls, analyze obstacles in their implementation and find solutions to overcome these obstacles.